2017
DOI: 10.1016/j.jmbbm.2016.04.035
|View full text |Cite
|
Sign up to set email alerts
|

Effects of poly (ε-caprolactone) coating on the properties of three-dimensional printed porous structures

Abstract: Powder-based inkjet three-dimensional printing (3DP) to fabricate pre-designed 3D structures has drawn increasing attention. However there are intrinsic limitations associated with 3DP technology due to the weak bonding within the printed structure, which significantly compromises its mechanical integrity. In this study, calcium sulphate ceramic structures demonstrating a porous architecture were manufactured using 3DP technology and subsequently post-processed with a poly (ε-caprolactone) (PCL) coating. PCL c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 60 publications
(63 reference statements)
1
4
0
Order By: Relevance
“…Similar behaviours for samples infiltrated with cyanoacrylate have been reported in Impens and Urbanic 16 and Zhou et al. 31 Figure 3 shows the typical stress–strain curves for the composites. Higher toughness is evidenced for the EP-infiltrated composite.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Similar behaviours for samples infiltrated with cyanoacrylate have been reported in Impens and Urbanic 16 and Zhou et al. 31 Figure 3 shows the typical stress–strain curves for the composites. Higher toughness is evidenced for the EP-infiltrated composite.…”
Section: Resultssupporting
confidence: 82%
“…Zhou et al. 31 achieved higher compressive strength (∼217%) using the poly ɛ-caprolactone coating technique of 3D-printed structures. The ultimate strain of the infiltrated epoxy composites (EP) was slightly higher than the PC (Table 6).…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of dimensional error and surface roughness demonstrates that the minimal error and roughness for FDM‐based AM was <5% with the anisotropic feature, strongly depending on the 3D printing orientation. Those significant results would benefit the fundamental design and manufacturing of integrated devices using 3D printing in the microfluidic application in the future [38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we demonstrated that the incorporation of 0.5, 1 and 2.5 wt% of nanosized mesoporous BGs in a PCL matrix via the in-situ ring opening polymerization of ε-caprolactone, resulted in a biocompatible PCL composite material with superior mechanical properties, accelerated biodegradation rate and bioactivity [63]. In this context, PCL/BG composites and nanocomposites are promising materials for a wide range of applications such as coatings for metallic or ceramic scaffolds for bone regeneration [64,65,66], as a solution for their high corrosion rates or low bioactivity, as root canal filling materials, or as bone scaffolds [15,63,67,68,69,70].…”
Section: Introductionmentioning
confidence: 99%